Lingguizhugan decoction improves non-alcoholic steatohepatitis partially by modulating gut microbiota and correlated metabolites - Zhu, Mingzhe; Wang, Xue; Wang, Kai; Zhao, Zhiqiang; Dang, Yanqi; Ji, Guang; Li, Fenghua; Zhou, Wenjun (Frontiers in Cellular and Infection Microbiology, 2023)
Background Lingguizhugan decoction is a traditional Chinese medicine prescription that has been used to improve non-alcoholic fatty liver disease and its progressive form, non-alcoholic steatohepatitis (NASH). However, the anti-NASH effects and underlying mechanisms of Lingguizhugan decoction remain unclear. Methods Male Sprague-Dawley rats were fed a methionine- and choline-deficient (MCD) diet to induce NASH, and then given Lingguizhugan decoction orally for four weeks. NASH indexes were evaluated by histopathological analysis and biochemical parameters including serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), liver triglycerides (TG), etc. Fecal samples of rats were subjected to profile the changes of gut microbiota and metabolites using 16S rRNA sequencing and ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MS). Bioinformatics was used to identify Lingguizhugan decoction reversed candidates, and Spearman’s correlation analysis was performed to uncover the relationship among gut microbiota, fecal metabolites, and NASH indexes. Results Four-week Lingguizhugan decoction treatment ameliorated MCD diet-induced NASH features, as evidenced by improved hepatic steatosis and inflammation, as well as decreased serum AST and ALT levels. Besides, Lingguizhugan decoction partially restored the changes in gut microbial community composition in NASH rats. Meanwhile, the relative abundance of 26 genera was significantly changed in NASH rats, and 11 genera (such as odoribacter, Ruminococcus_1, Ruminococcaceae_UCG-004, etc.) were identified as significantly reversed by Lingguizhugan decoction. Additionally, a total of 99 metabolites were significantly altered in NASH rats, and 57 metabolites (such as TDCA, Glutamic acid, Isocaproic acid, etc.) enriched in different pathways were reversed by Lingguizhugan decoction. Furthermore, Spearman’s correlation analyses revealed that most of the 57 metabolites were significantly correlated with 11 genera and NASH indexes. Conclusion Lingguizhugan decoction may exert protective effects on NASH partially by modulating gut microbiota and correlated metabolites.